GW24-e1109 Effects and mechanism of dendritic cell derived exosomes immunization against atherosclerosis in diabetic ldlr-/- mice. (1st October 2013) - Xin, Wang; Zhiqing, He; Ruizhen, Ji; Feng, Wu; Zongui, Wu; Chun, Linga
Abstract : Objectives: To investigate whether the immunisation of DC derived exosomes from AGE-LDL vaccinated ldlr -/- mice could attenuate atherosclerosis and explore relative mechanisms. Methods: AGE-LDL immunisations were given to six-week-old ldlr-/- mice, and then spleens were obtained for isolating dendritic cells derived exosomes. Mice were proceeded to the exosome immunisation procedure (either from dendritic cells of immunised or PBS injected mice), while PBS was used as control. Serum were analysed with FPLC. Atherosclerotic lesions in aortic roots were observed by oil red, Masson, MOMA-2 and α-SMA staining. And T helper lymphocytes and Treg in vivo were analysed by flow cytometry, serum antibodies and relative cytokines were detected by ELISA. Expressions of relative genes in spleens were investigated with qPCR. Results: Immunisation of DC derived exosomes from AGE-LDL vaccinated ldlr-/- mice could significantly attenuate atherosclerosis progression, with neither significant changes of serum lipid nor lipid distribution. Such immunisation strategies could modulate the immune response by inhibiting Th1 lymphocytes, and increase the protective AGE-LDL specific antibodies, and qPCR revealed that the t-bet and ifn-γ had a lower expression in immune group. Conclusions: Data from our study has verified that vaccination with dendritic cell derived exosomes against AGE-LDL could effectively attenuate atherosclerosis, which might represent a promising therapy for clinical patients with atherosclerosis.